PERILAKU NGEBUT DAN PERSEPSI PENGENDARA SUMATERA BARAT - Purnawan Purnawan; Titi Kurniati (Journal of Indonesia Road Safety, 2019)
Speeding behavior is one of the factors that could cause traffic accidents. Speeding is generally carried out based on certain reasons. This study aims to determine speeding behavior in Padang city and the driver's perception of speeding behavior. To get speeding behavior in the field, the spot speed survey was conducted, while to find out perceptions about speeding behavior, an online survey was conducted. The results of the survey data analysis showed that drivers were speeding at peak and not peak hours; the percentage of drivers speeding up even more during the afternoon and evening. The driver was speeding due to internal factors and external factors that simultaneously supported the driver to drive the vehicle with speeding. Perilaku ngebut merupakan salah satu faktor yang dapat menimbulkan kecelakaan lalu lintas, tindakan ngebut pada umumnya dilakukan atas dasar alasan tertentu. Penelitian ini bertujuan untuk mengetahui perilaku ngebut di kota Padang, dan persepsi pengemudi atas perilaku ngebut. Untuk mendapatkan perilaku ngebut di lapangan, dilakukan survai kecepatan setempat, sedang untuk mengetahui persepsi tentang perilaku ngebut dilakukan survai online. Hasil analisa data survai menunjukkan bahwa pengemudi ngebut pada jam puncak dan tidak puncak, persentase jumlah pengemudi ngebut semakin banyak pada saat sore dan malam hari. Pengemudi ngebut disebabkan adanya faktor internal dan faktor eksternal yang secara bersamaan mendukung pengemudi mengendarai kendaraan dengan ngebut.